The influence law of eccentric load on the performance of yielding bolt. Issue 7 (1st July 2020) - Tai, Yang; Xia, Hongchun; Huang, Shaoping; Meng, Jie; Li, Wei
Abstract : In order to adapt to the high stress and avoid the large deformation in roadways, the pre-stressed yielding bolt has been developed. Prior to the installation of the pre-stressed yielding bolt, boreholes need to be drilled. However, not all boreholes are perpendicular to the surface of the roadway, and the non-perpendicular holes make the pre-stressed yielding bolt exposed to eccentric loads. In order to reveal the influence of the eccentric load on the performance of the pre-stressed yielding bolt, some numerical simulations were carried out in this study. The influence of the eccentric load on the displacement–load relations, utilization rate of the yielding pipe, the plastic strains of the bolt components as well as the evolution of the absorptive capacity of the yielding pipe were analysed. The results are as follows: (i) eccentric loads affected the utilization rate of the yielding pipe, plastic strains of bolt components and the absorptive capacity was quite great when displacement was less than 2 mm, while these impacts could be neglected when displacement is greater than 2 mm; (ii) as the eccentric load increased, the yielding point and its corresponding displacement increased linearly while the yielding magnitude decreased linearly; and (iii) the eccentric load could be adjusted to control the yielding point and magnitude in order to meet the roadway support's requirement for the yielding bolt.